Further Study of the Polar Group's Influence on the Antibacterial Activity of the 3-Substituted Quinuclidine Salts with Long Alkyl Chains - Renata Odžak; Doris Crnčević; Antonio Sabljić; Lucija Krce; Antonela Paladin; Ines Primožič; Matilda Šprung (MDPI AG, 2023)
Quaternary ammonium compounds (QACs) are among the most potent antimicrobial agents increasingly used by humans as disinfectants, antiseptics, surfactants, and biological dyes. As reports of bacterial co- and cross-resistance to QACs and their toxicity have emerged in recent years, new attempts are being made to develop soft QACs by introducing hydrolyzable groups that allow their controlled degradation. However, the development of such compounds has been hindered by the structural features that affect the bioactivity of QACs, one of them being polarity of the substituent near the quaternary center. To further investigate the influence of the polar group on the bioactivity of QACs, we synthesized 3-aminoquinuclidine salts for comparison with their structural analogues, 3-acetamidoquinuclidines. We found that the less polar amino-substituted compounds exhibited improved antibacterial activity over their more polar amide analogues. In addition to their better minimum inhibitory concentrations, the candidates were excellent at suppressing Staphylococcus aureus biofilm formation and killing bacteria almost immediately, as shown by the flow cytometry measurements. In addition, two candidates, namely QNH2-C14 and QNH2-C16, effectively suppressed bacterial growth even at concentrations below the MIC. QNH2-C14 was particularly effective at subinhibitory concentrations, inhibiting bacterial growth for up to 6 h. In addition, we found that the compounds targeted the bacterial membrane, leading to its perforation and subsequent cell death. Their low toxicity to human cells and low potential to develop bacterial resistance suggest that these compounds could serve as a basis for the development of new QACs.